Development of a Low-cost, Comprehensive Recording System for Circadian Rhythm Behavior - Kwon, Jea; Park, Min Gu; Lee, Seung Eun; Lee, C. Justin (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2018)
Circadian rhythm is defined as a 24-hour biological oscillation, which persists even without any external cues but also can be re-entrained by various environmental cues. One of the widely accepted circadian rhythm behavioral experiment is measuring the wheel-running activity (WRA) of rodents. However, the price for commercially available WRA recording system is not easily affordable for researchers due to high-cost implementation of sensors for wheel rotation. Here, we developed a cost-effective and comprehensive system for circadian rhythm recording by measuring the house-keeping activities (HKA). We have monitored animal's HKA as electrical signal by simply connecting animal housing cage with a standard analog/digital converter: input to the metal lid and ground to the metal grid floor. We show that acquired electrical signals are combined activities of eating, drinking and natural locomotor behaviors which are well-known indicators of circadian rhythm. Post-processing of measured electrical signals enabled us to draw actogram, which verifies HKA to be reliable circadian rhythm indicator. To provide easy access of HKA recording system for researchers, we have developed user-friendly MATLAB-based software, Circa Analysis. This software provides functions for easy extraction of scalable "touch activity" from raw data files by automating seven steps of post-processing and drawing actograms with highly intuitive user-interface and various options. With our cost-effective HKA circadian rhythm recording system, we have estimated the cost of our system to be less than $150 per channel. We anticipate our system will benefit many researchers who would like to study circadian rhythm.
Keywords: ARVICANTHIS-NILOTICUS; CLOCK; SLEEP; WHEEL; MICE; ARCHITECTURE; LICKING; RODENTS; RAT